Macroeconomic Challenges for the Transition to the Economy 4.0 in Bulgaria (Научни трудове на УНСС, 2018)
The paper examines changes in the Bulgarian economy following the global financial and economic crisis of 2008 that affect the macroeconomic environment for making the transition to the Economy 4.0. The main identified obstacles to sustainable technological economic growth are subdued investments and still low credit activity, high intercompany indebtedness, and relatively low levels of personal income. Meanwhile, the ongoing structural change in employment, increase in numbers and in share within overall production of the IT and research companies, and growing export opportunities may have a positive effect on the digitalization of Bulgarian economy.